Gamma‐induction in frontotemporal dementia (GIFTeD) randomized placebo‐controlled trial: Rationale, noninvasive brain stimulation protocol, and study design. Issue 1 (3rd February 2022) - Assogna, Martina; Sprugnoli, Giulia; Press, Daniel; Dickerson, Brad; Macone, Joanna; Bonnì, Sonia; Borghi, Ilaria; Connor, Ann; Hoffman, Megan; Grover, Nainika; Wong, Bonnie; Shen, Changyu; et al.
Abstract: Introduction: Frontotemporal dementia (FTD) is a neurodegenerative disorder for which there is no effective pharmacological treatment. Recently, interneuron activity responsible for fast oscillatory brain activity has been found to be impaired in a mouse model of FTD with consequent cognitive and behavioral alterations. In this study, we aim to investigate the safety, tolerability, and efficacy of a novel promising therapeutic intervention for FTD based on 40 Hz transcranial alternating current stimulation (tACS), a form of non‐invasive brain stimulation thought to engage neural activity in a frequency‐specific manner and thus suited to restore altered brain oscillatory patterns. Methods: This is a multi‐site, randomized, double‐blind, placebo‐controlled trial on 50 patients with a diagnosis of behavioral variant FTD (bvFTD). Participants will be randomized to undergo either 30 days of 1‐hour daily tACS or Sham (placebo) tACS. The outcomes will be assessed at baseline, right after the intervention and at a 3‐ to 6‐months follow‐up. The primary outcome measures are represented by the safety and feasibility of tACS administration, which will be assessed considering the nature, frequency, and severity of adverse events as well as attrition rate, respectively. To assess secondary outcomes, participants will undergo extensive neuropsychological and behavioral assessments and fluorodeoxyglucose (FDG)–positron emission tomography (PET) scans to evaluate changes in brain metabolism, functional and structural magnetic resonance imaging (MRI), resting and evoked electroencephalography, as well as blood biomarkers to measure changes in neurodegenerative and neuroinflammatory markers. Results: The trial started in October 2020 and will end in October 2023. Study protocols have been approved by the local institutional review board (IRB) at each data‐collection site. Discussion: This study will evaluate the safety and tolerability of 40 Hz tACS in bvFTD patients and its efficacy on gamma oscillatory activity, cognitive function, and brain glucose hypometabolism.